Implementation of Religious Moderation Values in the School Environment to Foster an Attitude of Tolerance - Suma, I Made Markus; Tandiangga, Patrio; Palinoan, Frans Fandy; Patampang, Carolus (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The current reality in Indonesia shows that often intolerant attitudes still occur in the school environment. For example, cases of violence, bullying, religious discrimination and so on. Departing from this situation the author decided to conduct research about Implementation of Religious Moderation Values in the School Environment to Foster an Attitude of Tolerance. Implementing the values of religious moderation is an alternative effort to avoid conflict in society such as violence and discrimination from certain parties. Implementing the values of religious moderation will directly contribute to an attitude of religious tolerance, but must be supported by various parties in order to create a more moderate attitude. The aim of this research is to determine the effect of implementing religious moderation values on students' attitudes of religious tolerance. This research is a systematic litterature review. Researchers searched for and reviewed several literatures from the results presented in previous studies. Thus, the data examined in this research is in the form of literature from previous research that has been published. Strategy for collecting data using the Publish or Perish application. The results of this research show that implementing religious moderation among students is important because religious diversity cannot be eliminated. The basic idea of moderation is to look for similarities and not sharpen differences.